ETR300 Fundamental of Entrepreneurship: House of mushroom / Sthella Ak Brandah... [et.al] - Brandah, Sthella; Wan Mustapha, Syed Anwar Al'edrus; Manggi, Kevin Hop; Tasek, Hartiny; Ikum, Diana; Lawei, Tracy Haren (2010)
House of Mushroom is a partnership company which is aimed to be main supplier of the mushroom product. In every progressive firm or organization, top management is important to ensure responsibility for quantifiable, measurable, and attainable objectives. In order to ensuring our business plan is complete on the time, we have put our all effort in preparing this business proposal. The major business of our company are to produce variety of mushroom and also as main supplier of mushroom in Kuching and Samarahan area and our mission is that we want to spread our business at whole Sarawak and then until whole countries in Malaysia. House of Mushroom was located at NO.G1-5B, GROUND FLOOR & 1st FLOOR, DEMAK LAUT COMMERCIAL CENTRE, JALAN BAKO, 93050 KUCHING, SARAWAK. Our company established at year 2011. We registered our business on 1st January 2011. We start our capital around RM33984. We take loan as additional source of our capital at amount of RM120,000. In order to supply our mushroom product, we do plantation of several types of local mushroom first before we plant more types of mushroom from other foreign countries which are hard to find in Malaysia. From our analysis, mushroom supply is very hard to find in this business area, that is why we choose this business to supply the mushroom to all people who need mushroom in their daily activity. Furthermore we have been noticed that there is a high demand of mushroom in this area as there is no other mushroom supplier near this area. In this business we also promote our business at our own blog. Through this, we can promote and advertise our business quickly and more efficient to attract more customers. At the same time we also have create our own business card for easier connection with anyone who interested in our product. We also have banner and brochure for the customer to get direct information about our business.